Appendectomy and Pregnancy: Gestational Age Does Not Affect the Position of the Incision. Issue 3 (March 2015) - de Moya, Marc A.; Sideris, Antonios C.; Choy, Garry; Chang, Yuchiao; Landman, Wendy B.; Cropano, Catrina M.; Cohn, Stephen M.
The position of the base of the appendix during advancing gestational age is based on inadequate data. Therefore, the proper location for an appendectomy incision during pregnancy is highly unclear. This study investigated the location of the appendix during pregnancy to determine the optimal location for an incision in pregnant patients with appendicitis relative to McBurney's point. Magnetic resonance images (MRIs) were reviewed independently by two fellowship-trained abdominal MRI radiologists blinded to the imaging report. The distance of the appendix from anatomic landmarks was measured in a total of 114 pregnant women with an abdominal or pelvic MRI who were admitted between 2001 and 2011 at a Level I trauma center. Patients with a history of appendectomy were excluded. The distance from the base of the appendix to McBurney's point changed over the course of the gestation by only 1.2 cm and which did not amount to a clinically or statistically significant change in position. Our data provide evidence that there is minimal upward or lateral displacement of the appendix during pregnancy, and therefore its distance from the McBurney's point remains essentially unchanged. These findings justify the use of the McBurney's incision for appendectomy during pregnancy regardless of the trimester.